The Comparison Between Indonesia and The Netherlands Regarding Commercial Dispute Arbitration - Christ Sella; Januari Nasya Ayu Taduri (Journal of Private and Commercial Law, 2023)
In the dynamic realm of business, entrepreneurs continually encounter a multitude of risks and challenges that have the potential to lead to disputes among various parties involved. To effectively navigate such situations, businesspeople often prefer to adopt alternative dispute resolution methods, such as arbitration, rather than opting for traditional litigation. This preference is primarily motivated by a desire to protect and maintain the company's valuable reputation and goodwill. In Indonesia, the practice of arbitration dates back to the colonial era and is currently governed by The Act Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. In this paper, the author aims to conduct a comprehensive comparative analysis of arbitration mechanisms in Indonesia and the Netherlands. The main objective is to assess the progress of arbitration in Indonesia in comparison to other countries and explore innovative arbitration mechanisms that can be implemented to further enhance the effectiveness of dispute resolution. To achieve this goal, the research methodology employed for this legal analysis is normative legal research with a comparative approach. By utilizing this approach, the study seeks to gain a deeper understanding of the existing arbitration practices in both Indonesia and the Netherlands, identify strengths and weaknesses, and propose potential areas for improvement. Overall, this study endeavors to shed light on the advancements made in the field of arbitration in Indonesia while drawing insights from international practices. By exploring and adopting novel arbitration mechanisms, the hope is to contribute to the development and refinement of Indonesia's dispute resolution landscape for the benefit of businesses and stakeholders alike.